A dual ternary system for highly efficient ITO-free inverted polymer solar cells1. Issue 36 (28th September 2015) - Peng, Zuosheng; Xia, Yuxin; Gao, Feng; Xiong, Kang; Hu, Zhanhao; James, David Ian; Chen, Junwu; Wang, Ergang; Hou, Lintao
<x xml:space="preserve">Abstract</x> With a dual ternary system, the device performance was greatly increased due to a finer nanostructure and improved energy level alignments.